Determining the performance indicators of employing combined methods for removing space objects from near-earth orbits - Dron’, Mykola; Hilorme, Tetiana; Golubek, Aleksandr; Dreus, Andrii; Dubovik, Ludmila (Eastern-European Journal of Enterprise Technologies, 2022)
A methodology for assessing the relative effectiveness of alternative options for building space object diversion systems has been improved. An algorithm for assessing the effectiveness of the system of removal of space objects from near-Earth orbit based on the method of integral assessment is given. It makes it possible to simplify the process of optimal choice of the method to divert space objects and determine efficiency in the early phases of the life cycle of rocket and space technology objects. The use of the appropriate toolset makes it possible to build a system for assessing the effectiveness of projects for the removal of space objects from low Earth orbits using various diversion methods (active, passive, combined). The analysis of defining world indicators of evaluation of objects of rocket and space technology based on regulations by international space agencies has been carried out. An indicator of the total integrated relative efficiency of projects of space object diversion systems from low Earth orbits has been proposed, which makes it possible to build the removal of passive, active, and combined methods for leveling the risks of space activities. It is argued that the selected combined system using an autophagic launch vehicle could reduce environmental losses and, as a result, reduce compensation payments to owners of space objects. The possibilities of building combined systems with reusable engines have been considered in order to reduce such indicators as the period of diversion and reduction of operating costs due to fuel economy.